Climate Change Education: Why to Train to Cope With Environmental Uncertainty, Vulnerability and Complexity? - Núñez-Rodríguez, Jesús (2021)
The objective of this essay is to analyze the concepts of environmental uncertainty, vulnerability, and complexity in the scenarios of present and future climate change, and the essential role of the school in forming citizens with capacities for mitigation and adaptation. As this article takes into consideration the bet on education and the risks for the human species, it is addressed to teachers and their students to incorporate new constructs in cognitive, axiological, and procedural competencies as useful tools to survive in vulnerable, complex, and uncertain environments. The methodology to write the essay was based on the review of the concepts analyzed in studies conducted by international organizations related to climate science, and by researchers who report evidence in indexed journals and their subsequent assessment of applications in educational processes. As a synthesis of the discussion carried out, we conclude that the contemporary human society is worryingly exposed to drastic climate changes that increase the vulnerability of the poor population by affecting food production, availability of drinking water, the incidence of pests and diseases, and loss of human lives in extreme climate events. In this scenario, education emerges as one of the institutions called to train new generations to survive on a warmer planet and with an unknown demographic map due to gradual climate migrations in search for water, food, soil, and livable climates.